The I-35W Bridge collapse : a survivor's account of America's crumbling infrastructure - Brown, Kimberly J. (Journalist) (Potomac Books, an imprint of the University of Nebraska Press, 2018)
In The I-35W Bridge Collapse, Kimberly J. Brown combines memoir and exposé to provide a full account of the Minneapolis I-35W bridge collapse of August 1, 2007, and its aftermath.